A systematic review of strategies to recruit and retain primary care doctors. Issue 1 (December 2016) - Verma, Puja; Ford, John; Stuart, Arabella; Howe, Amanda; Everington, Sam; Steel, Nicholas
Abstract Background There is a workforce crisis in primary care. Previous research has looked at the reasons underlying recruitment and retention problems, but little research has looked at what works to improve recruitment and retention. The aim of this systematic review is to evaluate interventions and strategies used to recruit and retain primary care doctors internationally. Methods A systematic review was undertaken. MEDLINE, EMBASE, CENTRAL and grey literature were searched from inception to January 2015. Articles assessing interventions aimed at recruiting or retaining doctors in high income countries, applicable to primary care doctors were included. No restrictions on language or year of publication. The first author screened all titles and abstracts and a second author screened 20 %. Data extraction was carried out by one author and checked by a second. Meta-analysis was not possible due to heterogeneity. Results Fifty-one studies assessing 42 interventions were retrieved. Interventions were categorised into thirteen groups: financial incentives (n = 11), recruiting rural students (n = 6), international recruitment (n = 4), rural or primary care focused undergraduate placements (n = 3), rural or underserved postgraduate training (n = 3), well-being or peer support initiatives (n = 3), marketing (n = 2), mixed interventions (n = 5), support for professional development or research (n = 5), retainer schemes (n = 4), re-entry schemes (n = 1), specialised recruiters or case managers (n = 2) and delayed partnerships (n = 2). Studies were of low methodological quality with no RCTs and only 15 studies with a comparison group. Weak evidence supported the use of postgraduate placements in underserved areas, undergraduate rural placements and recruiting students to medical school from rural areas. There was mixed evidence about financial incentives. A marketing campaign was associated with lower recruitment. Conclusions This is the first systematic review of interventions to improve recruitment and retention of primary care doctors. Although the evidence base for recruiting and care doctors is weak and more high quality research is needed, this review found evidence to support undergraduate and postgraduate placements in underserved areas, and selective recruitment of medical students. Other initiatives covered may have potential to improve recruitment and retention of primary care practitioners, but their effectiveness has not been established.